The efficiency analysis of foundations for buildings with bearing walls for Lithuanian soil conditions - Sušinskas, Saulius; Turskis, Zenonas; Stasiškis, Andrius; Valickas, Jonas; Rudžionis, Žymantas (Journal of Civil Engineering and Management, 2014)
The paper deals with selection of foundations for bearing walls of residential buildings depending on the strength of soil and taking into account the economic benefit. Based on in-situ investigation of soil conditions in different Lithuanian regions and construction technologies, it was found that the cost of foundations comprise 2.5–6% of total costs, and takes up 6–10% of construction time. Strip and pile foundations were analysed taking into account dimensions and mode of production. The proposed case study model enables to save up to 30–50% of foundation costs. It has a significant influence on entire life cycle costs of.